2023
DOI: 10.1108/ejm-03-2022-0185
|View full text |Cite
|
Sign up to set email alerts
|

Color effects on AI influencers’ product recommendations

Abstract: Purpose This paper aims to theorize and investigate the use of effective color features in artificial intelligence (AI) influencers, an emerging marketing trend in the social media context. Design/methodology/approach By analyzing 6,132 pictures posted by ten AI influencers on Instagram, this paper examines the effect of warm colors in AI influencers’ social media posts on consumer responses, and how other color features may moderate the effect of warm color. In addition, two experimental studies reveal the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 107 publications
0
1
0
Order By: Relevance
“…Barli et al ( 2012 ) found that stores with soft lighting (vs. bright lighting) had increased in-store time and red interiors decreased the in-store time. Warmer colors were more appealing to consumers and generated more positive responses with increased perceived warmth and emotional trust (Chan et al, 2023 ). A blue background (vs. a yellow background) increased perceived enjoyment and concentration, which increased the purchase intention and revisit intention (Aboubaker Ettis, 2017 ).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Barli et al ( 2012 ) found that stores with soft lighting (vs. bright lighting) had increased in-store time and red interiors decreased the in-store time. Warmer colors were more appealing to consumers and generated more positive responses with increased perceived warmth and emotional trust (Chan et al, 2023 ). A blue background (vs. a yellow background) increased perceived enjoyment and concentration, which increased the purchase intention and revisit intention (Aboubaker Ettis, 2017 ).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%